High data-rate packet communications for cellular networks using CDMA algorithms and performance. - Kumar, S. (IEEE Journal on selected areas in communications)
The advantages of code division multiple access (CDMA) for cellular voice have become well known, and IS-95-based systems have now been widely deployed. Attention is now focused on higher data-rate packet services for cellular systems. Although many packet multiple access schemes have been studied over the years, researchers have often studied single cell performance and ignored reuse. Moreover, direct sequence spread spectrum (DSSS) has been considered unsuitable for high data-rate packet multiple access since spreading limits the permitted data rates, DSSS requires large overhead (preambles) for acquisition and requires closed-loop power control. In this paper, we describe a scheme for high data-rate packet service using CDMA that addresses all of the above problems and has been standardized in Revision B of IS-95. A low rate fundamental code channel is maintained that eliminates the need for long preamble and provides closed-loop power control. Reuse is managed by the infrastructure through a ?burst-level? admission control based on load and interference-level measurements at the base stations and mobiles. We report on the feasibility of such a burst-mode packet data service for cellular CDMA networks. The focus is not only on the performance of high data-rate users, but also on the impact on voice users sharing the CDMA band. We propose a multitiered performance analysis methodology consisting of a mix of static simulations, dynamic simulations at different time scales, and analytic methods to address the various feasibility issues: impact on coverage; capacity; power control; and effectiveness of burst admission algorithms. Based on the current study, we can conclude that the proposed approach is well suited for third-generation wideband CDMA systems being considered for standardization throughout the world